Mannose Treatment: A Promising Novel Strategy to Suppress Inflammation - Zhang, Wei; Cheng, Hao; Gui, Yuanyuan; Zhan, Qipeng; Li, Si; Qiao, Wenliang; Tong, Aiping (Frontiers in Immunology, 2021)
High glucose and fructose intake have been proven to display pro-inflammatory roles during the progression of inflammatory diseases. However, mannose has been shown to be a special type of hexose that has immune regulatory functions. In this review, we trace the discovery process of the regulatory functions of mannose and summarize all studies showing the therapeutic functions of mannose in inflammatory diseases. We conclude that treatment with mannose can suppress inflammation by inducing regulatory T cells, suppressing effector T cells and inflammatory macrophages, and increasing anti-inflammatory gut microbiome. By summarizing all the important findings, we highlight that mannose treatment is a safe and promising novel strategy to suppress inflammatory diseases, including autoimmune disease and allergic disease.